A comprehensive review on branched nanofibers: Preparations, strategies, and applications. Issue 1 (June 2022) - Zaarour, Bilal; Alhinnawi, Mohammed Firas
Engineering surface morphologies of nanofibers has been attracting significant consideration in numerous fields and applications. Among different methods of generating nanofibers, electrospinning is the most widely adopted technique owing to the ease of forming nanofibers with an extensive range of properties and its exceptional advantages, such as the variety of shapes and sizes, as well as the adaptable porosity of nanofiber webs. The branched structure is considered one of the most attractive structures for scientific researchers due to its outstanding properties (e.g., high-specific surface area and extremely tiny diameters of branched nanofibers). Therefore, this work is the first one that summarizes the strategies and methods, reported so far, of producing branched nanofibers of different materials. The material types, formation mechanisms, characterizations, and applications of the branched nanofibers generated through different techniques will be discussed in detail in this study. We believe this work can be served as an important reference for the preparations, strategies, and applications of the branched nanofibers.